Counseling on the Importance of Electrical Installation Safety in Tegalpanjang Village - Ilman Himawan Kusumah; Muhamad Shobirin; Eka Muhammad Haryadi; Adi Mulyadi; Ranti Nurdiansari (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2021)
Electricity has a very vital role in everyday life, therefore the electricity network must be properly maintained and protected, otherwise, not only disrupt the need for electricity  but it can also endanger human safety. One type of electrical hazard that often arises is fire that caused by the electrical equipment used was not under the PUIL Standard (General Requirements for Electrical Installation in Indonesia) and COE (Certificate of Operation Eligibility). Beside carelessly installation that not comply with regulations that often cause electrical short circuit.. The purpose of this community service is to provide knowledge about the safe and correct household electrical installations to residence of Tegalpanjang especially school student so they can also provide information to other community members about dangers and utilization of electricity as well as correct electrical installation. The result of this service activity is the participants has knowledge upgrading and understanding about the dangers and use of electrical installations to avoid fires caused by electrical short circuits.